The Effect of Fruit Audio Aroma Media on Basic Science Process Skills in Elementary School - Rohmatun, Isnaini Nur; Atmojo, Idam Ragil Widianto; Yulisetiani, Septi (Universitas Pendidikan Ganesha, 2023)
Basic science process skills are important for elementary school students. Basic science process skills can optimize students' critical thinking skills and scientific thinking skills. In addition, they can also train students to solve the problems they experience in everyday life. However, many students have not mastered these skills. Therefore, learning media is needed to optimize these basic science process skills. Therefore, it is necessary to create learning media to optimize these basic science process skills. One of the learning media that can be used to optimize the basic science process skills in elementary school students is Fruit Audio Aroma learning media. This study aimed to analyze whether there was an effect of the use of Fruit Audio Aroma learning media on the basic science process skills in elementary school students. This research was a quantitative experimental one-shot case study conducted by providing treatment to students. Data were collected through performance tests. Data analysis techniques were carried out through the non-parametric test through the Wilcoxon test. The results of the Wilcoxon test show that the use of Fruit Audio Aroma learning media affected elementary school students' basic science process skills. The results of this study are expected to contribute to educators' optimization of students’ basic science process skills.